(817) Programming Techniques and Economic Policy Models تقنيات البرمجة ونماذج السياسات الاقتصادية - Fahmi K. Bishay (INP, 2024)
The Study discusses the theory of economic policy, beginning with an introduction to Tinbergen's ideas and their impact on economic theory and policy. It explores programming techniques used in economic policy models, focusing on limitations and recent techniques. Additionally, it reviews economic policy models in programming setups, providing an agricultural model as an example. The text also includes hypothetical economic policy models in parametric programming formulations, such as variable targets analysis and analysis of variable objective function's weights. It further examines recursive programming and economic policy models, along with an introduction to stochastic linear programming and its applications in sensitivity analysis. The text concludes with final remarks and a bibliography.